Salicin alleviates periodontitis via Tas2r143/gustducin signaling in fibroblasts - Zhang, Zhiying; Zhou, Zhiyan; Liu, Jiaxin; Zheng, Liwei; Peng, Xian; Zhao, Lei; Zheng, Xin; Xu, Xin (Frontiers in Immunology, 2024)
Introduction Cells expressing taste signaling elements in non-gustatory tissues have been described as solitary chemosensory cells (SCCs) or tuft cells. These “taste-like” cells play a critical role in the maintenance of tissue homeostasis. Although the expression of SCC markers and taste signaling constituents has been identified in mouse gingivae, their role in periodontal homeostasis is still unclear. Methods Public RNA sequencing datasets were re-analyzed and further validated with RT-PCR/qRT-PCR and immunofluorescent staining to explore the expression of TAS2Rs and downstream signaling constituents in mouse gingival fibroblasts (MGFs). The specific action of salicin on MGFs via Tas2r143 was validated with RNA silence, heterologous expression of taste receptor/Gα-gustducin and calcium imaging. The anti-inflammatory effects of salicin against LPS-induced MGFs were investigated in cell cultures, and were further validated with a ligature-induced periodontitis mouse model using Ga-gustducin-null (Gnat3−/−) mice. Results The expression of Tas2r143, Gnat3, Plcb2, and TrpM5 was detected in MGFs. Moreover, salicin could activate Tas2r143, elicited taste signaling and thus inhibited LPS-induced chemokines expression (CXCL1, CXCL2, and CXCL5) in MGFs. Consistently, salicin-treatment inhibited periodontal bone loss, inflammatory/chemotactic factors expression, and neutrophil infiltration in periodontitis mice, while these effects were abolished in Gnat3−/− mice. Discussion Gingival fibroblasts play a critical role in the maintenance of periodontal homeostasis via “SCC-like” activity. Salicin can activate Tas2r143-mediated bitter taste signaling and thus alleviate periodontitis in mouse, indicating a promising approach to the resolution of periodontal inflammation via stimulating the “SCC-like” function of gingival fibroblasts.